The Historical Jesus and the Speech of Gamaliel (Acts 5.35–9) - Trumbower, Jeffrey A. (New Testament studies, 1993)
As a supplement to the careful analysis of early Christian texts, anyone studying the historical Jesus of Nazareth is inevitably drawn to make comparisons between him and other figures from the ancient world in general, and first-century Palestine in particular. Just what type of figure was he? For example, in his book, Jesus the Jew, Geza Vermes emphasizes Jesus' compatibility with the category of Jewish charismatic figures like Honi the Circle-drawer (perhaps a Galilean) and Hanina Ben-Dosa (definitely a Galilean). Morton Smith compares the actions and words of Jesus to the magical papyri and finds remarkable similarities to ancient magicians, thus the title of his book, Jesus the Magician. Smith, like Celsus 1800 years earlier, delights in showing how Jesus was just one of the many fakers and charlatans practising the magical arts in the first-century Mediterranean world. More recently, Burton Mack has argued that Jesus was a cynic sage like those found in Diogenes Laertius' Lives of Eminent Philosophers. In Mack's reconstruction, Jesus' thought was not eschatological, nor did Jesus intend to found a movement or movements devoted to himself; rather, he preached the flaunting of social conventions and criticized his culture in general terms, like other cynic philosophers.